PENERAPAN TEORI BELAJAR BRUNER DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS VI SD IT SALSABILA 8 PANDOWOHARJO - Dina Ayu Lestari; Lastari; Isna Ari Rahmawati; M. Rofi Fauzi (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2023)
The purpose of this study was to find out the application of learning mathematics at SD ITSalsabila 8 Pandowoharjo using the application of Bruner's learning theory by using concrete objects as media to make it easier for students to understand mathematical concepts. This research approach is a qualitative research with observation and interview research designs to find out how to apply mathematics learning at SD ITSalsabila 8 Pandowoharjo. The research subjects in this study were teachers who taught mathematics for class VI SD ITSalsabila 8 Pandowoharjo. The results showed that by applying Bruner's learning theory there was an increase in students' learning abilities in learning mathematics. This is because the learning process using concrete objects makes students more interested in learning, the presence of concrete objects also makes students more active. The use of concrete media can create a fun learning atmosphere and can motivate students to learn. Learning systems using media are more effectively applied to students because the use of concrete objects can bridge abstract mathematical concepts into concrete ones.